Pengaruh Pupuk Kandang dan Kesesuaian Varietas-Musim Tanam terhadap Hasil Padi Sawah - Pratiwi, Gagad Restu; Sumarno, Sumarno (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2014)
Adaptive variety and organic fertilizer are important components for rice cultural practices in a spesific agroecology. The research objectives were (1) to clarify the direct and the residual effect of manure on grain yield of rice, (2) to identify rice varieties most suitable for dry and for wet season planting. The research was conducted at Sukamandi Exp. Farm, West Java, during dry season (DS) of 2010 and wet season (WS) of 2010/2011, using a split-plot design with three replications. The main plots of DS experiment consisted of (1) recommended dosage of NPK (115 kg N + 50 kg P2O5 + 50 kg K2O/ha) and (2) 80% dosage of NPK + 5 t manure/ha. The WS experiment, main plots were (1) recommended NPK and (2) the residue of manure given in DS + 80% of the NPK. The subplots were fifteen improved varieties, each planted on plot 3.4 m x 5.4 m with 20 cm x 20 cm plant spacing. Data were collected for agronomic variables and grain yield. The DS 2010 experiment was attacked by brown planthopper (BPH), only two varieties, Inpari-8 and Inpari-13 were resistant, each yielded around 6 t/ha, while thirteen varieties were susceptible, yielded between 0.14 t to 3.9 t/ha. Application of 5 t manure/ha increased the averaged of biomass and grain yields by 9% and 10%, respectively, but were not consistent among varieties. In WS 2010/2011 experiment, the residual manure + 80% NPK decreased the averaged grain yield, but there was a significant interaction effect between fertilizer x variety. Seven varieties yielded less, six varieties yielded similar, and two varieties yielded more on the residual manure treatment, compared to that on no-manure treatment. Biomass weight, plant height, days to flowering, and days to harvesting, each was significantly correlated with grain yield. Five varieties were identified as suitable for WS planting, namely: Inpari-3, Inpari-10, Inpari-7, Ciherang, and Mekongga. When outbreak of BPH was suspected in the DS, Inpari-8 and Inpari-13 were suggested for planting. Suitable variety(ies) for season specific planting would optimize productivity, conversely, planting of unsuitable rice variety, during either DS or WS planting, would decreased the land production capacity.